Assessing Gonadotropin Receptor Function by Resonance Energy Transfer-Based Assays - Ayoub, Mohammed Akli; Landomiel, Flavie; Gallay, Nathalie; Jégot, Gwenhael; Poupon, Anne; Crépieux, Pascale; Reiter, Eric (Frontiers in Endocrinology, 2015)
Gonadotropin receptors belong to the super family of G protein-coupled receptors and mediate the physiological effects of follicle-stimulating hormone (FSHR) and luteinizing hormone (LHR) on the control of reproductive function. Upon hormone binding, they trigger complex signalling and trafficking mechanisms that are tightly regulated in concentration, time and space. Classical cellular assays often fail to capture all these dynamics. Here, we describe various resonance energy transfer-based assays (BRET and FRET) used to investigate the activation and regulation of FSHR and LHR in real-time and in living HEK293 cells. Indeed, the dynamics of heterotrimeric G protein activation, cAMP production, calcium release, β-arrestin2 recruitment and receptor internalization/recycling was assessed. Kinetics and dose-response analyses confirmed the expected pharmacological and signalling properties of the two receptors but revealed interesting characteristics when considering the two major pathways (cAMP and β-arrestin2). Indeed, the EC50 values were in picomolar range for cAMP production while nanomolar range was observed for β-arrestin2 recruitment as well as receptor internalization. Interestingly, the predicted receptor occupancy indicates that the maximal G protein/cAMP response occurs at less than 10 % of receptor occupancy whereas >90 % of activated receptors is required to achieve full ß-arrestin2 recruitment and receptor internalization. The rapid receptor internalization was also followed by a recycling phase. Collectively, our data reveal that ß-arrestin-mediated internalization and the subsequent fast recycling of receptors may provide a mechanistic ground to the “spare receptor” paradigm. More generally, the novel tools described here will undoubtedly provide the scientific community investigating gonadotropin receptors with powerful means to decipher their pharmacology and signalling with the prospect of pathophysiological and drug discovery applications.